The Influence of Service Quality and Product Quality on Customer Satisfaction at the D'beauty House Beauty Clinic - Fauziyyah Maulidiningsih; Rahmat Hidayat (Transpublika Publisher, 2024)
This research aims to analyze the influence of service quality and product quality on customer satisfaction at the D'Beauty House Clinic, Bogor. This research uses quantitative methods with the Partial Least Squares - Structural Equation Modeling (PLS-SEM) approach. Respondents consisted of 60 customers selected using purposive sampling techniques. Data was collected through a 5-point Likert scale-based questionnaire. The research results show that service quality has a positive and significant influence on customer satisfaction with a coefficient value of 0.476 and a p-value of 0.001. Product quality also has a positive and significant influence on customer satisfaction with a coefficient value of 0.354 and a p-value of 0.027. Apart from that, service quality has a more dominant influence than product quality. The R-square value of 0.633 indicates that service quality and product quality together explain 63.3% of the variation in customer satisfaction. These findings emphasize the importance of synergy between responsive service quality and reliable products to increase customer satisfaction. D'Beauty House Clinic is advised to improve employee training, product innovation and customer feedback management in order to maintain competitiveness in the competitive beauty industry. This research contributes to the literature regarding service quality, product quality, and customer satisfaction in the context of beauty clinics.